Trehalose reduces retinal degeneration, neuroinflammation and storage burden caused by a lysosomal hydrolase deficiency. Issue 8 (3rd August 2018) - Lotfi, Parisa; Tse, Dennis Y.; Di Ronza, Alberto; Seymour, Michelle L.; Martano, Giuseppe; Cooper, Jonathan D.; Pereira, Fred A.; Passafaro, Maria; Wu, Samuel M.; Sardiello, Marco
ABSTRACT: The accumulation of undegraded molecular material leads to progressive neurodegeneration in a number of lysosomal storage disorders (LSDs) that are caused by functional deficiencies of lysosomal hydrolases. To determine whether inducing macroautophagy/autophagy via small-molecule therapy would be effective for neuropathic LSDs due to enzyme deficiency, we treated a mouse model of mucopolysaccharidosis IIIB (MPS IIIB), a storage disorder caused by deficiency of the enzyme NAGLU (alpha-N-acetylglucosaminidase [Sanfilippo disease IIIB]), with the autophagy-inducing compound trehalose. Treated naglu –/ – mice lived longer, displayed less hyperactivity and anxiety, retained their vision (and retinal photoreceptors), and showed reduced inflammation in the brain and retina. Treated mice also showed improved clearance of autophagic vacuoles in neuronal and glial cells, accompanied by activation of the TFEB transcriptional network that controls lysosomal biogenesis and autophagic flux. Therefore, small-molecule-induced autophagy enhancement can improve the neurological symptoms associated with a lysosomal enzyme deficiency and could provide a viable therapeutic approach to neuropathic LSDs. Abbreviations : ANOVA: analysis of variance; Atg7 : autophagy related 7; AV: autophagic vacuoles; CD68: cd68 antigen; ERG: electroretinogram; ERT: enzyme replacement therapy; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; GFAP: glial fibrillary acidic protein; GNAT2: guanine nucleotide binding protein, alpha transducing 2; HSCT: hematopoietic stem cell transplantation; INL: inner nuclear layer; LC3: microtubule-associated protein 1 light chain 3 alpha; MPS: mucopolysaccharidoses; NAGLU: alpha-N-acetylglucosaminidase (Sanfilippo disease IIIB); ONL: outer nuclear layer; PBS: phosphate-buffered saline; PRKCA/PKCα: protein kinase C, alpha; S1BF: somatosensory cortex; SQSTM1: sequestosome 1; TEM: transmission electron microscopy; TFEB: transcription factor EB; VMP/VPL: ventral posterior nuclei of the thalamus